Performance and carbon emissions of a diesel/oxy-hydrogen dual-fuel engine with oxy-hydrogen injection variation under low and medium load conditions - Felayati, Frengki Mohamad; Prasutiyon, Hadi; Janah, Sholikhatul; Wijaya, Dimas Hadi; Saputra, Mukhammat Bayu; Semin, Semin (International Journal of Renewable Energy Development, 2024)
Reducing carbon emissions such as carbon dioxide (CO2) and carbon monoxide (CO) from diesel engines struggled with engine performance challenges and fossil fuel limitations. Besides, huge transportation such as ships hardly replaced diesel engines due to the higher thermal efficiency and low operation cost. Oxy-hydrogen gas, as a carbon-free gas, could potentially improve diesel engine performance and carbon emissions. Most of the studies tried to identify the effect of oxy-hydrogen induction into diesel engine combustion on performance and emissions. However, this study evaluated oxy-hydrogen injector sizes to the diesel engine performance and carbon emissions at several loads and several engine speed conditions. Overall, the result showed that the oxy-hydrogen gas injection into the diesel engine’s intake port improved the performance and carbon emissions compared to the single diesel fuel as a baseline. High engine performance with low carbon emissions could be achieved at low and medium engine load conditions with high engine speeds. Moreover, smaller oxy-hydrogen injector sizes were suitable for the medium engine load and vice versa, to improve the performance and carbon emissions. At low load, the engine performance improvement of engine torque, specific fuel consumption, and thermal efficiency were 1800 to 2200 rpm. Moreover, the CO2 and CO emissions reductions were also suitable with 2200 rpm with a bigger oxy-hydrogen gas injector (6 mm). Furthermore, at medium load, the engine performance improved at 1400 rpm but the CO2 and CO emissions were lower at 2200 rpm with a small oxy-hydrogen gas injector (4 mm). The engine operation at 2200 rpm with a 4 mm injector also improved the engine performance regarding carbon emissions reduction. However, injecting oxy-hydrogen gas into diesel engines had the potential to enhance the engine performance and reduce carbon emissions, moving closer to achieving zero emissions